Estudio de factibilidad para crear una empresa dedicada a la producción y comercialización de un desmanchador para prendas de vestir (2013)
This project shows the different studies that should be conducted to produce and market a stain remover for clothing in the city of Pereira. On the study of market main characteristics are set to take into account so that the product can be marketed; as well as a detailed analysis on the information gathered through surveys to determine the preferences of potential users of such goods, responding to the variables of the market as price, product, promotion and place. By means of the technical study determines the availability of raw material, capital as well as the location of the business in order to start the company. Similarly be unveiled the process necessary to produce the stain remover, complying with the standards required in relation with the material handling and conservation of the environment. Related to the administrative and legal study shows as it is the organizational structure of the company, as well as the different functions of each of the contributors, who work taking into account the key elements for a good performance (service - quality - profitability). The study indicates is made up the company (its mission, vision, objectives, values) also emphasizes the legal aspect for the establishment and functioning of the organization. Highlights the environmental benchmark to consider to invest this way minimizes the negative impact to the environment; It also mentions policies and programmes to make a rational use of resources in the enterprise. Finally addresses the financial study and the financial evaluation of investment, where the first specifies the initial investment that must be made, are quantified operational costs projected to five years and prepares basic States proforma. The second assesses the investment with existing financial mathematical methods, which determines the existing business opportunity and good conditions on which would operate the new company, especially for partners or investors.